Impact of Clinical Pharmacist Mediated Patient Counseling on Health Related Quality of Life in Rheumatoid Arthritis Patients in Healthcare Resource Limited Settings of India - Mudhaliar, Mohanraj Rathinavelu; Yiragamreddy, Samhitha Reddy; Ghouse, Ishrar Shaik Mohammad; Patta, Javeed; Tabula, Ushanandhini; Kumar, Praveen (Indian Journal of Pharmacy Practice)
Background: Rheumatoid arthritis is defined as a chronic, progressive, auto immune mediated systemic inflammatory disease that primarily affects synovial joints. The management of rheumatoid arthritis according to the American College of Rheumatology (ACR) aims in relieving pain and discomfort and ameliorate symptoms; arrest or limit disease progression and, if possible, reverse pathological changes; maintain mobility and function, and promote the best possible quality of life, were pharmacist role is considered significant. Materials and methods: The current prospective interventional study (quasi experimental design) was conducted in a secondary care hospital for a period of six months to evaluate the impact of clinical pharmacist mediated patient counseling on health related quality of life in rheumatoid arthritis. The study involved collection of data by administration of a questionnaires SF-36 health survey during the first visit through direct patient interview. After which counseling was provided regarding disease, drug and lifestyle modifications by using a patient information leaflet. At the second visit the same questionnaire was administered and the responses were documented, finally the comparative score was calculated and the improvement in quality of life was calculated. Results: Our study observed that there is a significant difference in the quality of life in rheumatoid arthritis in all the domains both physically and mentally after providing the patient education through the patient information leaflet and the mean quality of life score for baseline and follow up visits 28.98 ± 16.35, 41.17 ± 16.15, 37.5 ± 16.23 respectively. Conclusion: Pharmacist based patient education and counseling may have greater positive impact on the quality of life in rheumatoid arthritis patients.
Keywords: Prospective interventional study; Pharmacists; Patient counseling; Quality of life; Rheumatoid arthritis